Hispania Tierra de Roma: organización y gestión del suelo - Santapau Pastor, María Carmen (Panta rei, 2008)
In the present work we studied two Hispanic cadastral inscriptions. The inscriptions, with the archaeological information and the literary sources allow us to have conclusions about the organization and the management of the Hispanic land at the beginning of the Roman Empire as a result of the conquest and the land distribution in different peninsular urban centers.